The Role of Motivation on the Performance of Employees of UPT RSUD Sultan Syarif Mohamad Alkadrie with Job Satisfaction and Organizational Citizenship Behaviour as Mediating Variables - Fauzan*, Rizky; Rusminah, Rusminah (Universitas Syiah Kuala, 2024)
This study aims to examine the effect of motivation on the performance of employees of UPT RSUD Sultan Syarif Mohamad Alkadrie through job satisfaction and Organizational Citizenship Behaviour (OCB). This study used a quantitative method with Structural Equation Modeling (SEM) data analysis technique. The sample of this study was 100 employees of UPT RSUD Sultan Syarif Mohamad Alkadrie who were randomly selected. The results of this study showed that motivation had a significant effect on job satisfaction, OCB, and employee performance. In addition, job satisfaction and OCB also had a significant effect on employee performance. Thus, the hypothesis of this study was accepted. This study provides implications that to improve employee performance, motivation, job satisfaction, and OCB of employees need to be increased. This study also provides suggestions for further research.